Increased risk of respiratory events during endobronchial ultrasound examination in patients with reduced forced expiratory volume: a prospective observational study - Grünewaldt, Achim; Rohde, Gernot (Frontiers in Medicine, 2024)
Background The incidence of adverse events during endobronchial ultrasound is low. Nevertheless, it is unclear, whether patients with impaired pulmonary function have an increased risk of respiratory events during the intervention. Methods A monocentric prospective observational study was performed at the Department of Respiratory Medicine, University Hospital Frankfurt/Main, Germany. Adult patients undergoing an endobronchial ultrasound examination with propofol-sedation were included. Pre-interventional screening included pulmonary function testing, laboratory tests and electrocardiogram. The occurrence of hypercapnia >55 mmHg or reduced oxygen saturation <85% was defined as a respiratory event was recorded and compared between patients with normal and impaired pulmonary function tests. Results In total, 126 patients were included. Pulmonary function testing revealed a median FEV1 of 2.2 l (range 0.4–6.04l) and a predicted FEV1 of 79.5% (range 20–127.8%) respectively. The median FVC was 3.0 l (range 0.87–7.28l), the median predicted FVC was 82% (range 31.4–128.4%). In 72 examinations (60%) pCO2 levels >55 mmHg were measured. Transient oxygen desaturation <85% occurred in 31 cases (25.8%). The Mann Whitney U-test showed a significantly lower FEV1 (% predicted value) in patients with respiratory events (p = 0.007). ROC analysis identified a predicted FEV1 of 78.5% as the optimal cut-off with a sensitivity of 58% and a specificity of 71%. Using Z-score instead of predicted values, there was no significant association between a lower Z- score of FEV or FVC and hypercapnic or hypoxic events. However, both a lower absolute value of FEV1/FVC and a lower Z-score of the FEV1/FVC index were associated with the occurrence of respiratory events. In binary logistic regression analysis, we could not demonstrate any association with other relevant parameters (age, BMI, sedation dosage, sedation duration, or ASA-score). Conclusions An impaired forced expiratory volume is associated with the frequency of respiratory events during endobronchial ultrasound examination under propofol-sedation.